2012
DOI: 10.1523/jneurosci.0624-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Food Intake Adaptation to Dietary Fat Involves PSA-Dependent Rewiring of the Arcuate Melanocortin System in Mice

Abstract: Hormones such as leptin and ghrelin can rapidly rewire hypothalamic feeding circuits when injected into rodent brains. These experimental manipulations suggest that the hypothalamus might reorganize continually in adulthood to integrate the metabolic status of the whole body. In this study, we examined whether hypothalamic plasticity occurs in naive animals according to their nutritional conditions. For this purpose, we fed mice with a short-term high-fat diet (HFD) and assessed brain remodeling through its mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 46 publications
(64 reference statements)
5
69
0
1
Order By: Relevance
“…Dietary fat-induced neuronal remodeling has previously been reported in the hypothalamus (Benani et al 2012) and obesity has been found to have neurodegenerative effects in this nucleus (McNay et al 2012). Microglia activation is involved in neuronal circuit remodeling (Kettenmann et al 2013) and has been found to control HFD-induced hypothalamic inflammation and loss of neuronal function (Valdearcos et al 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Dietary fat-induced neuronal remodeling has previously been reported in the hypothalamus (Benani et al 2012) and obesity has been found to have neurodegenerative effects in this nucleus (McNay et al 2012). Microglia activation is involved in neuronal circuit remodeling (Kettenmann et al 2013) and has been found to control HFD-induced hypothalamic inflammation and loss of neuronal function (Valdearcos et al 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Leptin was found to additionally regulate the synaptic organization of orexin neurons in the LHA 95 , and ghrelin was shown to modulate synapse formation in the hippocampus 96 and ventral tegmental area (VTA) 97 . Furthermore, hypercaloric challenges in the form of a HFD was also found to induce synaptic remodelling in the ARC 98,99 . Interestingly, deviations in the synaptic inputs to satiety promoting POMC neurons might contribute to the difference in susceptibility of inbred mouse strains to DIO 98 .…”
Section: Central Fgf1 Effects — Possible Mechanismsmentioning
confidence: 93%
“…Consequently, the necessity to drive Pomc and ␣-MSH synthesis becomes less crucial to compensate for the state of positive energy balance as the mice begin to normalize their chow intake, despite the small but statistically significant increase in body weight. Whereas HFD has been studied as a mechanism for modifying POMC peptide content, other reports suggest that HFD induces alterations in synaptic scaffold proteins, as well as changes in the synaptic inputs to POMC neurons (3,45,60). However, the interplay between these mechanisms and POMC peptide synthesis is not clear.…”
Section: E910 Leptin-independent Diet Effects On Pomc Peptidesmentioning
confidence: 99%